2016
DOI: 10.1016/j.yjmcc.2016.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cardiac hypertrophy and remodeling through the dual-specificity MAPK phosphatases (DUSPs)

Abstract: Mitogen-activated protein kinases (MAPKs) play a critical role in regulating cardiac hypertrophy and remodeling in response to increased workload or pathological insults. The spatiotemporal activities and inactivation of MAPKs are tightly controlled by a family of dual-specificity MAPK phosphatases (DUSPs). Over the past 2 decades, we and others have determined the critical role for selected DUSP family members in controlling MAPK activity in the heart and the ensuing effects on ventricular growth and remodeli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
65
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(69 citation statements)
references
References 93 publications
1
65
0
3
Order By: Relevance
“…MAPKs are central signaling intermediates that coordinate diverse physiological and pathological events such as those occurring in cancer, inflammation, diabetes, memory, and cardiac remodeling (Liu and Molkentin, ). MAPK is activated by membrane receptors, or other ill‐defined stress‐sensing effectors, which subsequently activate three major pathways including the p38 MAPK, JNK, and ERK pathways.…”
Section: Discussionmentioning
confidence: 99%
“…MAPKs are central signaling intermediates that coordinate diverse physiological and pathological events such as those occurring in cancer, inflammation, diabetes, memory, and cardiac remodeling (Liu and Molkentin, ). MAPK is activated by membrane receptors, or other ill‐defined stress‐sensing effectors, which subsequently activate three major pathways including the p38 MAPK, JNK, and ERK pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, numerous studies have shown that several intracellular signaling pathways might affect the progression of cardiac hypertrophy [18,19]. Notably, it has recently been shown that the hyperactivation of MAPK signaling plays a crucial role in the development of cardiac hypertrophy [20]. JNK is a member of the MAPK pathway and its altered expression is associated with cardiac hypertrophy [21].…”
Section: Discussionmentioning
confidence: 99%
“…Ca 2+ plays a key regulatory role in the metabolic activity and systolic function of cardiomyocytes [12]. Therefore, we also 20 measured the intracellular Ca 2+ concentration with Fluo-3/AM. In this regard, laser confocal microscopy showed that in PE-treated cardiomyocytes, the intracellular Ca 2+ concentration was increased compared to that in controls and that HAT or JNK inhibition could reduce the PE-induced increase in intracellular Ca 2+ .…”
Section: Discussionmentioning
confidence: 99%
“…TNF‐α, a multifunctional cytokine, has been reported to activate inflammation via activating mitogen‐activated protein kinases (MAPKs) and the nuclear factor ( NF )‐ κB . MAPKs belong to a large family of serine/threonine‐specific kinases including c‐Jun N‐terminal kinase (JNK), ERK and P38 that are demonstrated to be associated with myocardial dysfunction, hypertrophy, fibrosis, and heart failure . The activation of the MAPK signal pathways is also involved in the pathogenesis of diabetic cardiomyopathy.…”
Section: Introductionmentioning
confidence: 99%